(untitled) (RevistAleph, 2014)
RESUMO: A constituição do habitus professoral em narrativas (auto)biográficas de professores do Colégio Militar de Campo Grande é o foco deste estudo. Compreendemos que o referido habitus somente é possível no exercício da docência, é a síntese do ser e estar na profissão docente (SILVA, 2003; 2005; 2009; 2010). Trata-se do modo como o professor estabelece a sua práxis como resultado de sua socialização no campo educativo. A metodologia envolveu entrevistas semiestruturadas/não-diretivas. Os professores produziram um relato (auto)biográfico com o tema: “Lembranças e vivências de Colégios Militares na minha prática docente”. O estudo revelou um modo peculiar de ser e estar professor nesse espaço, em especial devido aos deslocamentos pelo território, que imprimiram marcas decorrentes das saudades de familiares, da terra natal e intercorrências entre o profissional e o pessoal. Palavras-chave: habitus professoral; professor militar; migração laboral. ABSTRACT: The constitution of professorial habitus in teachers’ (auto)biographical narratives is the focus of this study (these teachers work in Military College of Campo Grande). We understand that that habitus is only possible in the teaching profession, is the synthesis of being and the teaching profession. (SILVA, 2003; 2005; 2009; 2010). This is how the teacher establishes his practice as a result of their socialization in the educational field.The methodology involved semistructured/ non-directive interviews. The teachers produced an (auto)biographical report with the theme: "Military Colleges’ memories and experiences in my teaching practice". The study revealed a peculiar way of being and acting teacher in this space, particularly due to displacement by territory, that printed marks resulting from longing for the family, the homeland and complications between professional and personal aspects. Key-words: professorial habitus; military teacher; labor migration.